Liczby pseudolosowe a symulacyjna wycena opcji - Oczadły, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main purpose of his article is to show the differences between methods of generating random numbers. To test this methods for using them in process of pricing option contracts, I've used idea of control methods test to compare this algorithms of producing random numbers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 56-64